Some Indian mushrooms of therapeutic importance - Verma, Raj N (Mushroom Research, 2012)
Use of wild edible/medicinal mushrooms in India during the pre-historic period finds references in ancient Vedic literature dating back to 3,000 B.C. ‘Soma’, a divine drink of immortality, extracted possibly from Amanita muscaria was known to the Aryans (Wasson, 1968). The tribals and natives of forests and hills of India are still using several wild mushrooms. Ganoderma lucidum, a common parasite on trees in the tropical areas of our country, has been in use by the tribals for the treatment of joint pains as a folk medicine. However, people from plains and urban areas are mostly unaware of the medicinal qualities of these mushrooms. Although consumption of cultivated mushrooms is gradually increasing in Indian cities and towns, but mostly for their culinary qualities and to some extent for their protein-content. Therapeutic properties of some medicinal mushrooms, known to occur in India are described along with their diagnostic characters and distribution in this country, so that they are further explored, conserved and utilized for the welfare of the humanity.